Internalisasi Islamic Worldview dalam Pendidikan Ekonomi Islam: Strategi Membangun Etos Kerja dan Kemandirian Generasi Muda Muslim - Ariyanto, Ariyanto; Tarno, Tarno; Sholekah, Umma Rohmah; Sumiran, Sumiran (Lembaga Yasin AlSys, 2025)
Global economic structural shifts driven by modern capitalism and technological advancements have increasingly shaped human lifestyles toward consumerism, materialism, and individualism. This phenomenon has had a significant impact on education systems, particularly Islamic economic education, which faces the challenge of cultivating Muslim generations who excel not only academically but also possess spiritual integrity and social responsibility. This article aims to explore the role of the Islamic Worldview as a comprehensive value framework in developing a transformative model of Islamic economic education. The study employs a qualitative approach using library research methods, drawing from key literature including books, scholarly journals, and contemporary Islamic documents. The findings reveal that integrating the Islamic Worldview into economic education promotes the internalization of core values such as tauhid, amanah, qana’ah, and khilafah within the curriculum, instructional strategies, and economic character formation. This approach has proven effective in fostering an Islamic work ethic and economic self-reliance rooted in spirituality, blessing, and justice. The study concludes that Islamic economic education grounded in the Islamic Worldview is both a relevant and urgent approach to shaping productive, self-reliant, and morally grounded Muslim individuals amid contemporary global challenges.